A perspective on complementary/alternative medicine use among survivors of hematopoietic stem cell transplant: Benefits and uncertainties. Issue 14 (14th April 2015) - Chakraborty, Rajshekhar; Savani, Bipin N.; Litzow, Mark; Mohty, Mohamad; Hashmi, Shahrukh
Abstract : The widespread use of complementary and alternative medicine (CAM) in cancer survivors is well known despite a paucity of scientific evidence to support its use. The number of survivors of hematopoietic stem cell transplant (HCT) is growing rapidly and HCT clinicians are aware that many of their patients use CAM therapies consistently. However, due to a paucity of data regarding the benefits and harms of CAM therapies in these survivors, clinicians are reluctant to provide specific recommendations for or against particular CAM therapies. A systematic literature review was conducted with a search using PubMed, the Cochrane Database of Systematic Reviews, and Ovid online for each CAM therapy as defined by the National Center of Complementary and Alternative Medicine. The search generated 462 references, of which 26 articles were deemed to be relevant for the review. Due to extensive heterogeneity in data and limited randomized trials, a meta‐analysis could not be performed but a comprehensive systematic review was conducted with specified outcomes for each CAM therapy. In randomized controlled trials, certain mind and body interventions such as relaxation were observed to be effective in alleviating psychological symptoms in patients undergoing HCT, whereas the majority of the other CAM treatments were found to have mixed results. CAM use is an understudied area in HCT survivorship and clinicians should convey the benefits and uncertainties concerning the role of CAM therapies to their patients. Cancer 2015;121:2303–2313. © 2015 American Cancer Society . Abstract : Recent data indicate that 354 million visits to complementary and alternative medicine (CAM) practitioners in 2007 cost Americans $33.9 billion in out‐of‐pocket costs for products and visit charges. CAM use is an understudied area of hematopoietic stem cell transplant survivorship, and clinicians should convey the risks and benefits of individual CAM therapies to their patients.